Method for preparing nanofiltration membrane based on interfacial polymerization of autocatalysis of molecular encapsulation nanocapsule
By using nanocapsules to encapsulate the monomer in the interfacial polymerization method and releasing the monomer through the autocatalytic interfacial polymerization process, the problem of uncontrolled pore size distribution caused by fast reaction speed in the interfacial polymerization method is solved, and the structural performance of the nanofiltration membrane is adjustable and the high selective separation effect is achieved.
Patent Information
- Application Number
- CN202411449663.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-17
AI Technical Summary
In the process of preparing nanofiltration membranes by interfacial polymerization, the crosslinking degree and pore size distribution caused by fast reaction speed are not controlled, resulting in uncontrollable separation performance.
The target monomer is encapsulated in nanocapsules through a molecular blocking strategy, and the monomer is released through an autocatalytic interfacial polymerization process to control its diffusion and reaction, improving the controllability of the preparation process.
The structural performance of the nanofiltration membrane is adjusted, the precise separation efficiency of mixed monovalent salts is improved, and the uniform pore size distribution and high selectivity of the membrane are ensured.
Smart Images

Figure CN119524634A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a nanofiltration membrane based on the self-catalytic interfacial polymerization of molecule encapsulated nanocapsules, belonging to the technical field of nanofiltration membrane preparation. Background Art
[0002] Accurate and rapid ion selective separation is essential in environmental, energy and resource-related applications. In applications such as byproduct recovery, seawater desalination, and hydrometallurgy, different mixed ion systems require the construction of appropriate processes to effectively separate target ions from impurity ions. Nanofiltration membranes have become one of the most effective ion separation technologies due to their high cost-effectiveness, environmental protection, and high precision. Based on the special separation mechanism of size exclusion and Dornan effect, nanofiltration membranes show ultra-high selectivity for ions and organics of different radii and charges. Nevertheless, due to the small difference in hydration radius and the same net charge, the precise separation of two similar ions is still technically challenging. Studies have shown that the difference in selectivity of different similar ions is based on the dehydration phenomenon. According to this theory, ions close to the membrane pores temporarily strip off and rearrange the water shells around them to fit more easily into the pores. The degree of dehydration of ions depends on the hydration energy of the ions. The weaker the hydration energy, the easier it is for the ions to dehydrate. In general, the difference in dehydration barriers depends mainly on the pore size of the membrane and the interaction between ions and membrane channels. In order to improve the selectivity of similar ions and achieve superselective ion separation, it is necessary to design membranes with highly uniform channels.
[0003] Polyamide-based nanofiltration membranes are prepared on porous support layers by interfacial polymerization (IP), a mature and energy-efficient preparation technology. In a typical interfacial polymerization process, amine monomers in aqueous solution diffuse into the organic phase and react violently with acyl chlorides at the water / organic interface. In general, the interfacial polymerization process is controlled by the diffusion of amine monomers in the reaction zone. During the membrane formation process, the diffusion resistance of the monomers in the reaction zone increases exponentially with the growth of the polyamide (PA) layer. Fluctuations in the diffusivity and diffusion flux of amine monomers lead to spatially heterogeneous polymerization. In addition, the structural properties of PA nanomembranes are also affected by the kinetics of the interfacial polymerization reaction. The formation of nanomembranes usually takes place within seconds to minutes. Although the fast reaction rate is beneficial for large-scale manufacturing, it also leads to uncontrolled cross-linking degree and pore size distribution. Therefore, the uncontrolled diffusion and fast polymerization reaction induce the formation of nanomembranes with multi-scale heterogeneity and non-uniform pore size, resulting in uncontrollable separation performance. Summary of the invention
[0004] The technical problem to be solved by this patent is that in the process of preparing nanofiltration membranes by interfacial polymerization, the degree of crosslinking and pore size distribution are uncontrolled due to the fast reaction speed. This patent encapsulates the target monomer and releases it into the environment through a molecular sealing strategy, thereby improving the controllability of the preparation process.
[0005] A method for preparing a nanofiltration membrane based on nanocapsule autocatalytic interfacial polymerization comprises the following steps: Step 1: preparing nanocapsules: slowly adding a solution containing di-tert-butyl dicarbonate to a solution containing polyethyleneimine, stirring, and obtaining a milky white dispersion; and obtaining nanocapsules by centrifugation, washing, and drying; Step 2: Prepare a molecularly encapsulated super-selective nanofiltration membrane: dissolve the nanocapsules in a co-solvent, immerse the base membrane in the nanocapsule solution, and then remove the excess solution and bubbles on the membrane surface; then apply an aqueous solution containing piperazine monomers to the surface of the base membrane, and then wipe off the residual solution on the membrane surface; then apply an oily solution containing acyl chloride monomers to the base membrane, and perform interfacial polymerization to obtain a nanofiltration membrane.
[0006] The molecular weight of polyethyleneimine ranges from 1200 to 2500 Da; the molar ratio of polyethyleneimine to di-tert-butyl dicarbonate ranges from 1:0.01 to 0.04.
[0007] The stirring time is 6-10 h; the centrifugal speed is 8000-12000 rpm.
[0008] The material of the base film is selected from polyimide, polyethersulfone, polysulfone, polyketimine, polyurethane, polyelectrolyte, cellulose, polyamide, aromatic ester, ceramic film, metal film, polyvinylidene fluoride, polyphthalamide, titanium oxide, silicon dioxide, aluminum oxide or zirconium oxide.
[0009] The piperazine monomer is selected from piperazine, piperazine-2-carboxylic acid, 1-(tert-butyloxycarbonyl)piperazine, 3,5-bis(acrylamido)piperazine or 3-mercaptopiperazine.
[0010] The acyl chloride monomer is selected from trimesoyl chloride, terephthaloyl chloride, 2,2',4,4'-biphenyltetracarboxylic acid chloride or 5-(dichlorophosphoryl)isophthaloyl chloride.
[0011] The base film is a polyimide base film prepared by a non-solvent induced phase inversion method.
[0012] In the step 2, the concentration of the nanocapsules is 0.05-1 wt %.
[0013] The co-solvent is an 8-12 wt % triethanolamine aqueous solution, the concentration of the piperazine monomer aqueous solution is 0.015-0.02 wt %, and the contact time is 1-5 min.
[0014] The concentration of the oil phase solution containing the acyl chloride monomer is 0.05-0.15 wt %, and the contact time is 10-20 s.
[0015] A nanofiltration membrane is prepared by the above preparation method.
[0016] Application of the above-mentioned nanofiltration membrane in liquid filtration.
[0017] The liquid filtration includes Mg 2+ and Li + or the separation of Ac- and Cl-. Beneficial Effects
[0018] The present invention pre-presses nanocapsules on a polyimide substrate, which can significantly improve the influence of the substrate structure non-uniformity on the selection layer, and is conducive to the preparation of defect-free nanofilms. In the present invention, the released amine reacts with the acyl chloride to produce sufficient hydrochloric acid, which can further promote the decomposition of the nanocapsules and the release of the amines. The amount of hydrochloric acid produced in the interfacial polymerization controls the disintegration of the nanocapsules and the release of the amines, thereby increasing the participation of the amines in the reaction. The orderly release of the amines can enhance the uniformity of the diffusion process, and construct the membrane surface structure and uniform pore size distribution, and the membrane exhibits adjustable structural characteristics and precise separation efficiency of mixed monovalent salts. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 : Molecular encapsulation to prepare ultraselective and highly uniform nanofiltration membranes for synergistic control of diffusivity and reaction processes.
[0020] Figure 2 : Synthetic route of nanocapsules.
[0021] Figure 3 : FTIR spectra of PEI and PEI@Boc.
[0022] Figure 4 : Characterization of the self-catalyzed interfacial polymerization process. (a) Schematic diagram of the preparation of the original polyamide membrane; (b) FTIR spectra of PI, PI / PEI@Boc, TFC and i-TFC-PEI@Boc membranes; (c) Narrow N1s XPS spectrum of i-TFC-PEI@Boc membrane; (d) Water contact angle of the membrane; (e) Zeta potential of the membranes with different pre-coated materials; (f, g) SEM morphologies of TFC and i-TFC-PEI@Boc membranes.
[0023] Figure 5 : (a) Size distribution of PEI; (b) Size distribution of PEI@Boc.
[0024] Figure 6 : Schematic diagram of the complete reaction process of the self-catalytic interfacial polymerization strategy.
[0025] Figure 7 : O and N contents of PEI@Boc films with different pre-coating amounts.
[0026] Figure 8 : Zeta potential of different membranes.
[0027] Fig. 9 : SEM images of i-TFC and i-TFC-PEI membranes.
[0028] Fig.10 :Evaluation of membrane performance. (a, b) Effects of different concentrations of PEI@Boc and PIP on the MgSO4 performance of i-TFC-PEI@Boc membranes; (c) Comparison of membrane performance of different pre-coating materials; (d) Schematic diagram of the self-catalytic interfacial polymerization process.
[0029] Fig.11 : Surface morphology characterization of the membrane. (ac) SEM images of membranes with different interfacial polymerization reaction times; (df) SEM images of membranes with different nanocapsule concentrations; (g,h) Schematic diagram of the formation of precisely controlled polyamide membranes by self-catalytic interfacial polymerization.
[0030] Fig.12 : SEM images of different PEI@Boc films.
[0031] Fig.13 : (a) Schematic diagram of the gas measurement device made in the laboratory; (b) The displacement volume caused by the gas produced by traditional and novel autocatalytic interfacial polymerization processes.
[0032] Fig.14 : Characterization of the nanostructure of the membrane. (ac) Cross-sectional views of i-TFC, i-TFC-pei, and i-TFC-PEI@Boc; (d) UV-visible (UV-vis) spectra of PIP in the organic phase after diffusion on PI (solution only), PI / PEI, and PI / PEI@Boc for 120 s; (e) Average heat release rate of TEOA / PIP, TEOA-PEI / PIP, and TEOA-PEI@Boc / PIP solutions upon addition of TMC / hexane solution measured by ITC analysis (negative heat release rate represents exothermic behavior); (f) Pore size distribution of the membrane under different pre-coating materials.
[0033] Fig.15 : TMC / hexane solution was added to TEOA / PIP, TEOA-PEI / PIP and TEOA-PEI@Boc / PIP.
[0034] Fig.16 : Performance of i-TFC-PEI@Boc membrane for single salt solution.
[0035] Fig.17 : Separation performance of membranes. (a) Separation performance of i-TFC-PEI@Boc membrane for Ac- and Cl- at different pH values (1000:1000pm, 6 bar); (b) Separation performance of i-TFC-PEI@Boc membrane for mixed salts with different feed concentrations; (c) Long-term stability of the membrane for mixed salt separation; (d) Performance comparison with similar ion separation membranes reported; (e) Schematic diagram of the membrane separation mechanism of Ac- and Cl-; (f) Relationship between the retention of different solutes in i-TFC-PEI and (g) i-TFC-PEI@Boc and the Stokes radius; (h) Separation performance of MgCl2 and LiCl at different feed ratios. DETAILED DESCRIPTION
[0036] The following materials are used in the following examples: Polyamide PI (P84 ® ), polyethylene glycol (PEG, MW=400 Da) and N-methylpyrrolidone were used as polymer, non-solvent additive and solvent of coating solution, respectively, to prepare membrane substrate. Di-tert-butyl dicarbonate ((Boc)2O) was used as encapsulant to encapsulate polyethyleneimine (PEI, MW=1800Da) used as active agent, and dichloromethane (DCM, AR) was used as solvent in the synthesis of nanocapsules. Triethanolamine (TEOA) was used as co-solvent to improve the solubility of nanocapsules in water. Polyamide layer was prepared using nanocapsules, piperazine (PIP), trimesoyl chloride (TMC) and n-hexane to improve the selectivity of membrane. Example
[0037] Synthetic nanocapsules (PEI@Boc) PEI 1800 (5 g, 2.78 mmol) and (Boc)2O (10.4 g, 0.048 mol) were dissolved in DCM and stirred at a certain speed. After the solution was uniform, the (Boc)2O solution was slowly added to the PEI 1800 The solution was stirred at 25 °C for 8 h, and then the milky white dispersion was collected. The dispersion was centrifuged at 10,000 rpm and washed three times to remove residual impurities. The white powder obtained after drying was nanocapsules, which were denoted as PEI@Boc.
[0038] Preparation of molecularly encapsulated ultra-selective nanofiltration membranes The PI-based film was prepared by non-solvent-induced phase inversion method. The PI was dried in a vacuum oven at 60 °C for 10 h to remove moisture, and then the PI particles were dissolved in a mixed solution of NMP and PEG 400 (concentration percentages were 20%, 64%, and 16%, respectively). The coating solution was stirred for 12 h. After the solution was uniform, it was left for 10 h to remove the bubbles present in the solution, and the solution was cast on a non-woven fabric with a 100 μm thick knife. The prepared substrate was washed with deionized (DI) water to remove the residual solvent and stored in DI water before use.
[0039] Preparation of molecular encapsulated superselective nanofiltration membranes. In the process of self-catalytic interfacial polymerization, all nanofiltration membranes are pre-coated with nanocapsules, and then a trace amount of amine monomers is used as an initiator to produce HCl to release active monomers, achieving interfacial polymerization with coordinated control of diffusion and reaction. The specific preparation process is as follows: 0.1 wt% PEI@Boc powder is dissolved in 10 wt% TEOA solution and stirred for 2 h; further, in the comparative experiment, the above concentration is adjusted to change the concentration of PEI@Boc from 0.02 wt% to 0.5 wt%. After the solution is mixed evenly, the PI base film is immersed in PEI@Boc, and then a soft rubber roller is used to remove excess solution and bubbles on the membrane surface. Next, PIP is added to the surface of the base film in a very small amount as an initiator. The steps are to pour 0.0175 wt% PIP solution on the newly prepared membrane for 2 minutes, and then wipe off the residual solution on the membrane surface. Then, the membrane was immersed in a 0.1 wt% TMC / hexane solution for 20 seconds and immediately washed with hexane to quench the interfacial polymerization reaction. The prepared membrane was denoted as i-TFC-PEI@Boc and stored in deionized water for use. The i-TFC-PEI@Boc membrane preparation process is different from traditional interfacial polymerization. The byproduct HCl produced by the triggering reaction can maximize the release of self-catalyzed amine monomers to participate in the interfacial polymerization reaction, and then continue to generate HCl to promote the interfacial polymerization reaction and realize the construction of the membrane structure.
[0040] Comparative experiment In order to carry out comparative analysis, three nanofiltration membranes were prepared for comparison with i-TFC-PEI@Boc membrane. The first type, a membrane prepared without pre-coating with PEI@Boc solution but using only trace amounts of PIP and TMC, is labeled as TFC, and the specific parameters are the same as those in Example 1.
[0041] The second one was pre-coated with 10% TEOA (without PEI@Boc) aqueous solution, and the prepared membrane was labeled as i-TFC.
[0042] The third type was pre-coated with 10% TEOA solution dissolved with PEI (PEI concentration 0.1%), and the prepared membrane was labeled as i-TFC-PEI.
[0043] Characterization methods The diffusion rate of the monomer was detected by UV spectrophotometry. 10 ml of PEI or PEI@Boc dissolved in 10wt% TEOA solution was first pre-loaded on the PI substrate layer for 3 minutes, and the residual solution was wiped off. Then, 10 ml of 0.02wt% PIP / water solution was poured on the treated PI base film for 2 minutes, and the solution was removed. Finally, 10 ml of hexane was poured on the membrane for 20 seconds, and the hexane solution was transferred to a test tube to monitor the content of PIP. For comparison, 10 wt% TEOA solution was also pre-coated on the PI base film to exclude the effect of the solution on the diffusion of PIP.
[0044] Heat release rate experiments were evaluated by isothermal titration calorimetry. 100 μl of 0.0175 wt% PIP / water solution was slowly injected into 100 μl TEOA solution, 0.1wt% TEOA-PEI and 0.1 wt% TEOA-PEI@Boc, respectively. 0.1wt% TMC / hexane solution (40 μl) was poured into the syringe. The titration was performed at 25 °C, and 2 μl of TMC / hexane solution was injected 30 times each time. The initial injection was 0.4 μl to minimize the volume error caused by residual liquid on the syringe. During the measurement, the syringe was raised by 1 cm to ensure that the needle was above the surface of the PIP / water solution. Each injection was performed at a fixed time interval of 90 seconds. Control ITC experiments were previously performed using pure hexane and water to exclude the influence of the solvent. During the experiment, no stirring was performed to ensure interfacial reaction.
[0045] The concentration of positively charged ions in the mixed salt is measured by the ICP method. Ion chromatography is used to analyze the concentration of negatively charged ions in the mixed solution. In addition, the concentration of single ions is measured by a conductivity meter, and the concentration of acetate ions is measured by a total organic carbon analyzer.
[0046] To further confirm the self-catalytic interfacial polymerization process, the nanobubbles produced by the new process and traditional interfacial polymerization were measured and compared. Fig.13 ). The amount of CO2 gas generated reacts by increasing the volume of the solvent. First, 15 ml of 0.1wt% PEI@Boc solution and 15 ml of 0.0175 wt% PIP solution were added to the flask, and then 2 ml of 0.1wt% TMC solution was injected into the sealed system via a syringe. For the conventional interfacial polymerization process, only 0.0175 wt% PIP solution was added to the flask before injecting TMC. The amounts of PIP, PEI@Boc and TMC were consistent with those used in the membrane manufacturing process.
[0047] The pore size distribution of the membranes was analyzed using four neutral solutes of different molecular weights (MW), including raffinose, sucrose, glucose, and diethylene glycol. The molecular weight is related to the Stokes radius of the solute ( r s ) can be calculated by the following equation:
[0048] The pore size distribution of the membrane was calculated by the following equation:
[0049] in r p is the geometric mean radius corresponding to 50% retention rate, indicating the effective pore size; μ p is the average effective pore size, s p is the geometric standard deviation, which determines the sharpness of the pore size distribution.
[0050] Comparison and analysis of nanocapsule polyamide membranes Nanocapsules (PEI@Boc) were synthesized using PEI (Mw=1800) and di-tert-butyl dicarbonate (Boc)2O as raw materials. Figure 2 ). 1594 cm -1 The NH peak at 1684 cm -1 A new secondary amide peak appeared at , which strongly proved the successful introduction of (Boc)2O ( Figure 3 ). The size distribution of the particles increased from 2.24 nm to 82.91 nm, which can also prove the synthesis of nanocapsules ( Figure 5 ). When preparing the polyimide membrane, 10% TEOA was used as the dissolving solution PEI@Boc, which was first pre-loaded on the surface of the polyimide membrane. TEOA increased the solubility of the nanocapsules by reducing the surface tension of the solution. Then a trace amount of PIP was poured on the membrane as an initiator to react with trimethylol chloride (TMC). The above method is conducive to the orderly progress of the interfacial polymerization reaction. ( Figure 2 (a) and Figure 6 ). Elemental and functional group analysis confirmed the concept of autocatalysis ( Figure 7 and Figure 4 (b) and (c) of the Figure 2. After pre-coating with PEI@Boc, the contents of O and N increase with the increase of PEI@Boc concentration, which is due to the presence of ester groups in (Boc)2O and amine groups in PEI ( Figure 7 ). In addition, Figure 4 As shown in (b), the film spectrum is at 3250 cm -1The PI / PEI@Boc film shows a broad absorption band at 1065 cm due to the carbonyl peak of (Boc)2O. -1 After interfacial polymerization, all prepared polyamide membranes showed peaks at 1613, 1540, and 1451 cm -1 Obvious bands appeared at all locations, which was due to the formation of the polyamide network. In the concentration range of 0~0.1%, the intensity of the peak increased due to the influence of the degree of interfacial polymerization reaction. It is worth noting that when the concentration of PEI@Boc increased to 0.1%, the peak at 2360 cm -1 A new band appears at 398.5 eV, which may be due to the release of CO2 during the disintegration of the nanocapsules, and some CO2 molecules are trapped in the dense polyamide network. The XPS peak at 398.5 eV corresponds to the N1s nuclear energy level spectrum of primary amines, confirming that the nanocapsules will disintegrate and release reactive amines to participate in the interfacial polymerization process ( Figure 4 (c)).
[0051] The membranes prepared by the self-catalytic interfacial polymerization method have significantly different properties. The presence of -OH in the TEOA solution improves the hydrophilicity of i-TFC-PEI@Boc compared to the PI-based membrane and TFC membrane. After the interfacial polymerization reaction, the i-TFC-PEI@Boc membrane showed stronger hydrophilicity than the i-TFC membrane. This can be attributed to the fact that the HCl produced during the interfacial polymerization process releases the amines of PEI, which is beneficial to enhance the hydrophilicity ( Figure 4 (d)). The improvement of hydrophilicity is beneficial to the permeability of the membrane. The negative charge of i-TFC-PEI@Boc membrane is less than that of other membranes ( Figure 4 (e)). For TFC and i-TFC membranes, the lower the PIP concentration, the fewer amino groups participate in the reaction, and more acyl chlorides remain on the membrane surface. The acyl chlorides will hydrolyze, causing the membrane to have more negative charge. In i-TFC-PEI@Boc and i-TFC-PEI membranes, -NH reacts more with TMC. However, the nanocapsules absorb the HCl produced during interfacial polymerization, and the autocatalytic process promotes the reaction more thoroughly. Therefore, the i-TFC-PEI@Boc membrane has a high degree of reaction and less unreacted acyl chlorides remain on the membrane surface. Therefore, the i-TFC-PEI@Boc membrane has the least negative charge. Similarly, the positive charge of the membrane increases with the increase of nanocapsule content ( Figure 8 At the same time, due to the trace concentration of PIP, the surface of the TFC membrane is no different from that of the PI-based membrane ( Figure 4 (f)). After TEOA pre-coating, the i-TFC membrane surface only showed limited nodular structural features. When PEI was pre-coated onto the membrane surface, these structures gradually increased due to the increase in the degree of reaction ( Fig. 9). The Turing structure can be seen from the i-TFC-PEI@Boc film ( Figure 4 (g). During the autocatalytic interfacial polymerization, the active monomers are provided by the disintegration of the nanocapsules. The on-demand release of monomers enhances the uniformity and controllability of amine diffusion, but also restricts the free diffusion of monomers, resulting in changes in the membrane structure.
[0052] The improved performance reflects the increased degree of polyamide network reaction and also indicates that the HCl produced during the interfacial polymerization will decompose the nanocapsules and then release the amine to participate in further interfacial polymerization. When the initiator concentration is as low as 0.0175%, the membrane rejection rate of MgSO4 is still high ( Fig.10 (b)). Specifically, the reaction with TMC requires only a limited amount of initiator to produce enough HCl to catalyze the decomposition of the nanocapsules and release reactive groups. The released amine participates in the interfacial polymerization process and releases HCl, which continues to catalyze the release of the nanocapsules and the interfacial polymerization reaction. Finally, through the self-limiting effect, the polymerization rate slows down significantly with the increase of the polyamide thickness, and a uniform, defect-free nanofilm can be obtained through self-regulation ( Fig.10 (d)).
[0053] Comparative analysis with three comparison membrane materials ( Fig.10 (c)). When no deposition occurs on the membrane, trace amounts of PIP cannot fully react to form defect-free polyamide nanomembranes, so the TFC membrane does not retain MgSO4. Since -OH exists in TEOA, it can react with TMC, so when only TEOA is pre-coated, the retention rate of the i-TFC membrane is 68.4%. In addition, when PEI is deposited on the membrane surface and compared with the case where no deposition occurs, although the retention rate of i-TFC-PEI for MgSO4 is 90%, it is still lower than that of i-TFC-PEI@Boc. This is because HCl is consumed during the release of the nanocapsules, and the degree of self-catalytic interfacial polymerization reaction increases, resulting in a denser membrane structure of i-TFC-PEI@Boc.
[0054] Analysis of membrane morphology, structure and performance The polyamide nanofilm prepared by self-catalytic interfacial polymerization is very different from the nodular structure of traditional polyamide membranes in morphology. The disintegration of nanocapsules and the release of active monomers are closely related to the interfacial polymerization time. Therefore, the content of PEI@Boc was controlled at 0.1%, and the effect of interfacial polymerization time on the imaging of nanochain structure was studied. Fig.11As shown in (a)-(c), when the interfacial polymerization reaction lasts for 10 s, a small amount of nodular structures appear on the membrane surface. However, as the polymerization time increases, the Turing structure gradually forms until the entire membrane surface is covered. The reasons for the morphological changes are as follows: (1) When the polymerization time is short, the initiator PIP mainly reacts with TMC, and the surface presents a typical nodular structure. However, due to the low PIP concentration, the surface only shows limited nodular structures. (2) The formation of the polyamide layer is a self-catalytic interfacial polymerization process. The HCl produced in the polymerization reaction will continue to catalyze the decomposition of the nanocapsules and enter the next reaction cycle. The interfacial polymerization process mainly depends on the amines released after the disintegration of the nanocapsules to react with TMC. Only after sufficient HCl is produced in the first cycle reaction can the nanocapsules decompose and release the amine groups, enter the next cycle, and finally realize the polymerization reaction. This process inhibits the diffusion of amine monomers, and the difference in diffusion characteristics between the activator and the inhibitor leads to the appearance of the Turing structure. (3) As the reaction time increases, the monomers are continuously released, the restricted diffusion of the monomers becomes more and more obvious, and the nanochain structure gradually grows until it covers the membrane surface ( Fig.11 ).
[0055] In addition, with the increase of PEI@Boc concentration, the density of nanochain structure increased significantly after 30 s of reaction. When the content of PEI@Boc reached 0.5 wt%, irregular nanobubbles appeared on the membrane surface ( Fig.11 (d) and (f) and Fig.12 ). Specifically, there are three aspects to the evolution of the nanofilm surface structure. First, during the autocatalytic interfacial polymerization, the order of monomer release significantly improves the diffusion process of active monomers transferred to the organic phase, leading to the formation of nanochain structures. The consumption of HCl and the absorption of heat caused by the disintegration of nanocapsules lead to changes in concentration and thermal gradients in the water / organic interface, resulting in unstable convective flows. The fluctuating interface may also be responsible for the formation of the nanochain structure. In addition, during the disintegration of nanocapsules, in addition to active amines, a small amount of CO2 and isobutylene are produced. As the concentration of nanocapsules increases, the degree of reaction can be enhanced, and the gas cannot pass through the dense polyamide network, leading to the formation of a nanobubble structure ( Fig.11 To verify the accuracy of the above results, the volume change of the solvent caused by the self-catalytic interfacial polymerization reaction was measured in a sealed flask. Compared with the traditional interfacial polymerization process, the solvent volume increased significantly after the introduction of nanocapsules ( Fig.13 ). This can be explained by the disintegration of the nanocapsules producing additional CO2 gas.
[0056] Analysis of the Effect of Reactive Monomers on Membrane Thickness and Pore Size The change in the diffusion coefficient of the reactive monomers leads to a reduction in the reaction zone, which is conducive to the thinning of the polyamide layer and the improvement of mass transfer efficiency. Therefore, the change in membrane thickness was also studied. Fig.14 As shown in (a)-(c), the thickness of the polyamide layer of the i-TFC-PEI@Boc membrane is significantly reduced compared with that of i-TFC and i-TFC-PEI. The reasons for the thickness change can be divided into two stages: the initial membrane formation stage and the membrane generation stage with diffusion-limited growth behavior. In the first stage, PIP diffuses into the oil phase as an initiator to react with TMC. When PIP diffuses more into the organic phase, it accumulates less in the support layer. Reduced PIP penetrates the PI layer, reducing the invasion of polyamide into the pores of the substrate. The concentration of PIP in the organic solution was determined by UV-visible spectrophotometry with a fixed time of 30 s, and PIP showed a maximum absorption peak at about 220 nm. When PEI or PEI@Boc is pre-coated, the diffusion rate of PIP is greatly improved due to the competitive diffusion of different monomers ( Fig.14 (d)). Therefore, compared with i-TFC, i-TFC-PEI and i-TFC-PEI@Boc exhibit thinner selective layers, which is caused by the synergistic effect of the reduction of PIP penetration through the support layer and the increase in the diffusion rate to the organic phase. In addition, the concentration of amine groups in i-TFC-PEI and i-TFC-PEI@Boc is much higher than that in the i-TFC membrane, so it is easier to form a dense polyamide layer in the early stage of the reaction, thereby inhibiting the subsequent diffusion of monomers into the organic phase. This is another reason why i-TFC-PEI and i-TFC-PEI@Boc exhibit thinner polyamide layers. Once a continuous membrane is formed, the reaction enters the second stage. The monomer diffuses through the initial polyamide nanomembrane at a significantly reduced rate and slowly thickens the membrane. The heat release rate of the interfacial polymerization process plays an important role in the formation of polyamide nanomembranes. Strong heat release will increase the local temperature, causing "interfacial boiling" and accelerating the interfacial polymerization process. As Fig.14 (e) and Fig.15 As shown in the figure, the introduction of nanocapsules greatly increased the average heat release rate, thus showing a higher resistance to heat dissipation from the aqueous phase during the interfacial polymerization process. In addition, after the introduction of nanocapsules, the byproduct HCl produced during the polymerization process was absorbed during the disintegration of the nanocapsules, allowing more amines to react with TMC, thereby releasing more heat. The enhanced heat release performance promoted the highly active interfacial polymerization process. The reduction in diffusion rate and the acceleration of local reaction rate simultaneously led to the shrinkage of the reaction zone, which ultimately led to the thinning of the thickness of i-TFC-PEI@Boc.
[0057] The release of reactive monomers mediated by nanocapsules can effectively regulate the diffusion transport of amines at the water / organic interface and improve the kinetics of the interfacial polymerization process, which is a necessary condition for the formation of nanomembranes with uniform pore size distribution. Fig.14As shown in (f), the geometric standard deviation of i-TFC-PEI@Boc is 1.28, and the pore size is narrower and the pore size distribution is more uniform compared with i-TFC and i-TFC-PEI membranes. Due to the enhanced degree of nanomembrane reaction, the pore size of the membrane decreases with the increase of nanocapsule content. Because the disintegration process of nanocapsules acts as a promoter of interfacial reactions, it will change the transport of water / organic interface. Due to the uniformity of diffusion flux and the uniformity of spatial polymerization, the pore size distribution of the polyamide layer is more uniform.
[0058] Separation mechanism and performance analysis of ions Ion selectivity, especially for ions with similar hydration radius and net charge, is of great significance for the application of nanofiltration in wastewater resource recovery and seawater desalination. The retention rate of the membrane was tested using five single salts. Fig.16 As shown in the figure, the i-TFC-PEI@Boc membrane has a 2+ and SO4 2- The removal rate of Na + The removal rate of NaAc and Cl- is low. The separation performance of the membrane was evaluated by a cross-flow nanofiltration device using a binary solute mixture composed of NaAc and NaCl produced during the post-treatment of Pigment Yellow 12. Different pH conditions of the feed solution have a significant effect on the separation system. Fig.17 As shown in (a), the membrane rejection rate for Cl- is less than 20% in the pH range of 2-10. In contrast, when the pH of the feed solution increases from 2 to 10, the membrane's inhibition of Ac- ions increases, indicating that the membrane fully separates the two ions.
[0059] Different concentrations of feed solution were measured at the original neutral pH. Fig.17 As shown in (b), in both cases, the membrane has high selectivity for Ac- and Cl-, and high selectivity for Cl - The retention rate of Ac- is about 10%, while the retention rate of Ac- is greater than 95%. This can be attributed to the fact that the polyamide nanomembrane will enhance some mass transfer, thereby improving the back diffusion of solutes to the body and reducing concentration polarization, thereby improving the separation performance of the membrane. In addition, long-term filtration tests of the membrane showed that excellent separation performance can be achieved even after 120 h ( Fig.17 (c)).
[0060] By pre-coating nanocapsules, the solute separation behavior of polyamide nanomembranes has been significantly improved. Fig.17As shown in (f), based on the synergistic effect of Donnan and steric sieves, the i-TFC-PEI membrane has a wide range of solute rejection in the Stokes radius. At the same time, the solute adsorption of the i-TFC-PEI@Boc membrane depends largely on the Stokes radius of the ion. r s A sharp transition occurs at ~ 2.5 Å ( Fig.17 The reduction in the transition range enables precise separation of ions with sub-1 Å selectivity. Fig.17 (h) shows the feed liquid Mg 2+ / Li + Effects of concentration ratio and salt concentration on the separation performance of i-TFC-PEI@Boc membrane. 2+ / Li + The ratio increased from 10 to 50, and the feed solute ion concentration increased from 5.5 g / L to 25.5 g / L. 2+ The interception rate of Li + The interception rate is about 10%.
Claims
1. A method for preparing nanofiltration membrane based on molecular encapsulation nanocapsule autocatalytic interfacial polymerization, characterized in that: The steps include: Step 1: preparing nanocapsules: slowly adding a solution containing di-tert-butyl dicarbonate to a solution containing polyethyleneimine, stirring, and obtaining a milky white dispersion; and obtaining nanocapsules by centrifugation, washing, and drying; Step 2: Preparation of molecularly encapsulated superselective nanofiltration membrane: dissolving nanocapsules in a co-solvent, immersing the base membrane in the nanocapsule solution, and then removing excess solution and bubbles from the membrane surface; Then, an aqueous solution containing piperazine monomers is applied to the surface of the base film, and then the residual solution on the surface of the film is wiped off; Then, an oil phase solution containing acyl chloride monomers is applied on the base film to carry out an interfacial polymerization reaction to obtain a nanofiltration membrane.
2. The method for preparing nanofiltration membrane based on molecular encapsulation nanocapsule autocatalytic interfacial polymerization according to claim 1, characterized in that: The molecular weight of polyethyleneimine ranges from 1200 to 2500; the molar ratio of polyethyleneimine to di-tert-butyl dicarbonate ranges from 1:0.01 to 0.04; the stirring time is 6 to 10 h; and the centrifugal rate is 8000 to 12000 rpm.
3. The method for preparing nanofiltration membrane based on molecular encapsulation nanocapsule autocatalytic interfacial polymerization according to claim 1, characterized in that: The material of the base film is selected from polyimide, polyethersulfone, polysulfone, polyketimine, polyurethane, polyelectrolyte, cellulose, polyamide, aromatic ester, ceramic film, metal film, polyvinylidene fluoride, polyphthalamide, titanium oxide, silicon dioxide, aluminum oxide or zirconium oxide; The piperazine monomer is selected from piperazine, piperazine-2-carboxylic acid, 1-(tert-butyloxycarbonyl)piperazine, 3,5-bis(acrylamido)piperazine or 3-mercaptopiperazine; The acyl chloride monomer is selected from trimesoyl chloride, terephthaloyl chloride, 2,2',4,4'-biphenyltetracarboxylic acid chloride or 5-(dichlorophosphoryl)isophthaloyl chloride.
4. The method for preparing nanofiltration membrane based on molecular encapsulation nanocapsule autocatalytic interfacial polymerization according to claim 1, characterized in that: The base film is a polyimide base film prepared by a non-solvent induced phase inversion method.
5. The method for preparing nanofiltration membrane based on molecular encapsulation nanocapsule autocatalytic interfacial polymerization according to claim 1, characterized in that: In the step 2, the concentration of the nanocapsules is 0.05-1 wt %.
6. The method for preparing nanofiltration membrane based on nanocapsule autocatalytic interfacial polymerization according to claim 1, characterized in that: The co-solvent is an 8-12 wt % triethanolamine aqueous solution, the concentration of the piperazine monomer aqueous solution is 0.015-0.02 wt %, and the contact time is 1-5 min.
7. The method for preparing nanofiltration membrane based on molecular encapsulation nanocapsule autocatalytic interfacial polymerization according to claim 1, characterized in that: The concentration of the oil phase solution containing the acyl chloride monomer is 0.05-0.15 wt %, and the contact time is 10-20 s.
8. A nanofiltration membrane, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the nanofiltration membrane according to claim 8 in liquid filtration.
10. The use according to claim 8, characterized in that: The liquid filtration includes Mg 2+ and Li + or the separation of Ac- and Cl-.
Citation Information
Patent Citations
Polyimide nanofiber composite membrane, preparation method and application of polyimide nanofiber composite membrane in organic solvent nanofiltration process
CN112452168A
Preparation Method of Polyamide Thin Film Composite Reverse Osmosis Membrane and Polyamide Thin Film Composite Reverse Osmosis Membrane Prepared Therefrom
US20080234462A1
Solvent resistant polyamide nanofiltration membranes
US20130112619A1